Impact of ZnO nanoparticle morphology on relaxation and transport properties of PLA nanocomposites. (May 2019) - Lizundia, Erlantz; Penayo, Marie Cristina; Guinault, Alain; Vilas, Jose Luis; Domenek, Sandra
Abstract: In this work we study the effect of zinc oxide (ZnO) nanoparticle morphology and concentration on the resulting relaxation and transport properties of polylactide (PLA) nanocomposites. Films containing spherical and rod-shaped ZnO nanoparticles were incorporated into an amorphous polylactide (PLA) matrix through a solvent-precipitation and compression moulding method. Morphological analyses carried out by scanning electron microscopy (SEM) together with ultraviolet–visible (UV-Vis) spectroscopy and thermogravimetric analysis (TGA). Results indicate a much better distribution of rod-shaped ZnO within PLA matrix. Relaxation experiments reveal faster physical aging kinetics of PLA in presence ZnO nanoparticles notwithstanding their shape, suggesting the presence of non-interacting surfaces between the amorphous PLA matrix and the ZnO nanoparticles. Interestingly, both helium and oxygen permeability remained stable or increase upon nanoparticle addition, and anisole sorption kinetics showed faster mass transport in the nanocomposites, suggesting that the low interfacial adhesion between PLA and ZnO brings supplementary voids to the material increasing mass transport. Overall, the experimental findings here reported provide a deeper understanding on the influence of metal oxide nanoparticle morphology on the resulting relaxation and gas transport properties of amorphous polymeric nanocomposites. Graphical abstract: Image 1 Highlights: Relaxation and transport properties of PLA nanocomposites are studied. Spherical and rod-shaped ZnO nanoparticles were incorporated into amorphous PLA. Faster physical aging kinetics of PLA in presence ZnO nanoparticles are observed. Anisole sorption kinetics reveal faster mass transport in the nanocomposites. Low PLA-ZnO interfacial adhesion determines relaxation and gas transport behaviour.